Hospital management strategy in the aspect of visualization of the pandemic COVID-19 - Kanownik, Greta (Journal of Education, Health and Sport, 2021)
The article addresses an important issue regarding the impact of the coronavirus pandemic on the operation of hospitals and the use of management strategies at the present time and in reality after the pandemic. Based on the analysis performed, the article indicates four key areas that require immediate action to improve the functioning of the health care system and maintain the public health of the population. Based on the analysis of 9 crisis levers of the business model of A. Osterwalder, Y. Pigneur, four main areas requiring immediate intervention were identified, namely: development of medical personnel, development of computerization and digital competences, optimization of revenues and costs, identification of decision-making centers - appropriate division of tasks and responsibility. In these areas, the Polish health care system has failed, they require urgent strengthening and strategic long-term solutions, which will translate into optimization of activities aimed at securing the health of the society. It turns out that during the pandemic, it was not costs that turned out to be the biggest problem, but above all staff shortages, lack of access to health services, or equipment and organizational shortages. The time of the pandemic has shown that the researchers' theories that quality and not cost are the most important have proved successful. According to M.E. Porter and E. Teisberg, despite the limitations, the health care system can achieve excellent results in terms of both quality and effectiveness, which, however, often requires transformation and implementation of new competition rules aimed at increasing the value created.